A Structural Equation Model of Academic Literacy and Critical and Reflective Thinking Dispositions* - Demir, Sezgin; Deniz, Hacer (Hacettepe Univ, 2025)
Academic literacy requires metacognitive skills, such as reading and understanding academic texts, analyzing, making inferences, problem solving, and the ability to create text in academic language. These processes are thought to be effective on both critical and reflective thinking. The purpose of this research is to determine the relationship between pre-service teachers' academic literacy skills and their reflective and critical thinking dispositions. The research employs a relational model, one of the quantitative research methods. The research sample, determined by the cluster sampling method, consists of 975 students studying in Turkish teaching departments of universities in seven different regions of Turkey during the 2019-2020 academic year. While the latent variables of academic disposition and use of knowledge explained 10% of reflective thinking according to the study, this rate increased to 12% when critical thinking was added to the predictor in the first model. Academic literacy of teacher candidates as measured by latent variables of academic disposition and use of knowledge explains 12% of their critical thinking in second model. However, when reflective thinking is added to this equation, it was observed that the rate of prediction increased to 14%. Thus, both models tested were confirmed to be accurate.
Keywords: Academic literacy; critical thinking; reflective thinking